Penyusunan Target Penjualan dengan Menggunakan Metode Autoregresive Integrated Moving Average(ARIMA)Box Jenkins - Sumarsono (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
Market conditions are becoming increasingly competitive in order to exist in the midst of market competition without exception must improve the right business strategy by developing a strategy plan of planning and development, especially those related to the market. Marketing Department, especially the sales department has an important role as the spearhead of the company in competing in the market. One of the major sales plans is to make sales targets. It is expected that the sales target is a realistic figure with the current market condition and certainly still consider the growth aspect in the target year based on the previous year.The method used in the preparation of sales targets using the method Autorgresive Integrated Moving Average (ARIMA)Box Jenkins. The results of the analysis obtained sales predictions for 52 weeks ahead. And considering the annual growth factor of 20% obtained value of sales target 52 weeks ahead. With the measured sales target value, the sales target value becomes realistic and the achievement of the sales target will be better realized. Furthermore, the marketing can develop a strategy of achieving the target with more clearly and directed by considering the condition of people's purchasing power, the level of brand competition in the year of prediction and team readiness and cost expenses.